Pengaruh Motivasi Karir dan Persepsi Mahasiswa Akuntansi terhadap Minat untuk Mengikuti Pendidikan Profesi Akuntansi (PPAK): (Studi Empiris pada UMMY Solok) - Defitri, Siska Yulia (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2016)
This study aimed to examine the effect of career motivation and perception of acconting students to enthusiasm following the accounting profession edutation (PPAK) at the university mahaputra Muhammad yamin solok. The population used is whole accounting students enrolled in the second semester of 2014/2015 academic year at the university mahaputra Muhammad yamin, while the sample is selection criteria for accounting students who have followed the course of auditing 1. The type of data used are primary data. The analytical method test, multiple linear regression, f test, t test, and the coefficient of determination. The results showed that the variables of career motivasion and student perceptions of accounting silmultan no influence on interest following the accounting profession education (PPAK). Partially career motivation significantly influence following the accounting profession education (PPAK) and the perception of accounting students a significant effect on the interest to follow the accounting profesission education.